Sediment trap and deep sea coretop sediments as tracers of recent changes in planktonic foraminifera assemblages in the southeastern ultra-oligotrophic Levantine Basin. (January 2020) - Avnaim-Katav, Simona; Herut, Barak; Rahav, Eyal; Katz, Timor; Weinstein, Yishai; Alkalay, Ronen; Berman-Frank, Ilana; Zlatkin, Olga; Almogi-Labin, Ahuva
Abstract: Sediment trap and core top sediments were used to study the seasonal and longer-term variability in the distribution and assemblage composition of planktonic foraminifera (PF) in the ultra-oligotrophic Eastern Mediterranean Levantine Basin (LB). A continuous time series of particulate flux sampled every 11–12 days were retrieved from a sediment trap deployed at 1300 m between May 2017 and May 2018. The core top sediments were collected close to the sediment trap mooring site at ~1500 m water depth. The average annual planktonic foraminiferal (PF) flux was 93 shells m -2 d -1, the lowest value yet recorded among traps located in tropical-subtropical oligotrophic regions. A bimodal increase in PF flux is observed, with highest numbers of 452 shells m -2 d -1 occurring in winter (February), responding directly to maxima in particulate mass flux. A lower flux occurs in late summer from mid-August to mid-September with up to 197 shells m -2 d -1 . Ten species were found in the trap, the majority were symbiont-bearing spinose species that contribute 96% of the total flux. Globigerinoides ruber white predominate the assemblage composition during the winter peak together with Globoturborotalita rubsecens and Globigerinella calida . During the subordinate summer peak the dominating species were G. ruber white, Orbulina universa and Globigerinoides ruber pink. The relative abundance of G. bulloides and G. ruber pink is much lower in the sediment trap samples compared to their abundance in nearby coretop sediments. This trend seems to indicate a recent drop in their numbers. At the same time G. rubescens and Globoturborotalita tenella occur in higher numbers in the sediment trap compared with the coretop samples. These opposite trends may reflect the current adjustment of certain PF species to the ongoing sea surface warming and decrease in food availability in the LB.